Cat and dog predation on birds: the importance of indirect predation after bird-window collisions - Rebolo, Natalia (2021)
Predation of free-living birds by cats (Felis silvestris catus) and dogs (Canis lupus familiaris) is one of the main urbanization impacts on avifauna worldwide. In addition to direct predation, these pets capture birds after window collisions, an unexplored human cause of avian mortality. In this study we (1) estimated the number of cats and dogs in Argentina, (2) calculated the metrics of direct bird predation by cats and dogs, (3) analyzed factors that influence the probability of pets capturing birds, and (4) estimated annual bird mortality due to pet predation following bird-window collision events. To this end, we conducted an online survey to collect information on bird predation by cats and dogs in Argentina, both direct and indirect after bird-window collisions. We found that more than 68% of participants had at least one dog or cat, and of these, 45.3% reported having observed at least one case of bird predation by cats or dogs in their household. We estimated that the rough annual bird mortality rate due to predation following bird-window collisions could reach approximately 6 million birds in Argentina (range = 1–11 million birds). Our results show that direct bird predation by pets but also indirect predation after bird-window collisions represents a considerable source of avian mortality, which requires further attention in pursuit of solutions.